2014
DOI: 10.1039/c4ra02743d
|View full text |Cite
|
Sign up to set email alerts
|

A facile solvent-free route to synthesize ordered mesoporous carbons

Abstract: A novel solvent-free route is developed to synthesize a series of highly ordered mesoporous carbons (OMCs) and functionalized OMCs from solid raw materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…14,19 The so template method has become one optimal choice since the solvent-free route to OMCs avoids organic solvents. 26 OMCs based on the so template method have been developed to gain enhanced lithium storage performance, such as reversible capacity and initial coulombic efficiency. 15 In the past decade, heteroatom-doped (such as boron, [27][28][29] nitrogen, [29][30][31][32][33][34][35] phosphorous, 29,36 and sulfur 37 ) porous carbons have been proposed as active materials for electrochemical catalyzed oxygen reduction reaction, 29,36,37 supercapacitors, 27,28,31,32,35,38 dyesensitized solar cells, 33 CO 2 capture 34,35 and batteries.…”
Section: Introductionmentioning
confidence: 99%
“…14,19 The so template method has become one optimal choice since the solvent-free route to OMCs avoids organic solvents. 26 OMCs based on the so template method have been developed to gain enhanced lithium storage performance, such as reversible capacity and initial coulombic efficiency. 15 In the past decade, heteroatom-doped (such as boron, [27][28][29] nitrogen, [29][30][31][32][33][34][35] phosphorous, 29,36 and sulfur 37 ) porous carbons have been proposed as active materials for electrochemical catalyzed oxygen reduction reaction, 29,36,37 supercapacitors, 27,28,31,32,35,38 dyesensitized solar cells, 33 CO 2 capture 34,35 and batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported a solvent-free synthesis method for the preparation of ordered mesoporous carbons and their nitrogen-doped counterparts . It was observed that the CO 2 capture capacity and selectivity of these carbon materials are improved after nitrogen doping which results from the increase of their surface polarity and surface basic sites. , However, the intensity of interactions between CO 2 molecules and nitrogen groups are still not strong enough.…”
Section: Introductionmentioning
confidence: 99%
“…22 Although NH 4 F is not considered as a template for synthesizing zeolitic materials, recent studies demonstrate its cooperation with tetrapropylammonium bromide (TPABr) can lead to the formation of many types of zeolites in solvent-free condition. [23][24][25] Because of the similarity between dissolution and crystallization of zeolites, a dissolution process is reasonably expected by using a combination of organic ammonium salt and NH 4 F in the solvent-free condition. In this work, introduction of secondary porosity into Silicalite-1 zeolite is succeeded in a solvent-free approach by grinding calcined zeolite with TPABr and NH 4 F. The strategy preserves the high crystallinity and microporosity of the pristine zeolites, and forms mesopores at room temperature and macropores at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%